Kegiatan Outing Class Sebagai Sarana Pengembangan Sosial Emosional Anak Usia Dini Di TK Mardi Luhur - Fasya, Linda Ayu; Alwi, Itsnaini Muslimati (Lembaga Yasin AlSys, 2025)
The development of early childhood social-emotional skills is a crucial aspect in shaping children's character and readiness to engage with their social environment. One effective effort to support this development is through outing class activities, which provide direct and contextual learning experiences outside the classroom. This study aims to explore how outing class activities are implemented at TK Mardi Luhur and to understand their benefits for the social-emotional development of young children. The research employed a qualitative descriptive approach with a case study design. Data collection techniques included participatory observation, in-depth interviews, and documentation studies. The results show that outing class activities at TK Mardi Luhur are systematically designed by considering learning objectives, location selection, and active involvement of teachers and parents. The benefits of these activities are evident in children's improved abilities to interact socially, manage emotions, build self-confidence, and foster independence. The study concludes that outing class activities significantly contribute to the social-emotional development of early childhood. The implication of this research highlights the importance of well-planned outing class activities to support the holistic development of children in early childhood education settings.